2008
DOI: 10.1186/cc7145
|View full text |Cite
|
Sign up to set email alerts
|

Tight perioperative glucose control is associated with a reduction in renal impairment and renal failure in non-diabetic cardiac surgical patients

Abstract: Introduction Acute renal failure after cardiac surgery increases in-hospital mortality. We evaluated the effect of intra-and postoperative tight control of blood glucose levels on renal function after cardiac surgery based on the Risk, Injury, Failure, Loss, and End-stage kidney failure (RIFLE) criteria, and on the need for acute postoperative dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
3
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 37 publications
(42 reference statements)
1
52
3
1
Order By: Relevance
“…Nonetheless, some preoperative and intraoperative preventive actions may help to prevent the postoperative renal dysfunction. Postponing the operation to improve the hemodynamic situation [19], stopping medications, such as angiotensin-converting enzyme inhibitors/angiotensin receptor blockers, shortly before the operation [20], planning the surgical strategy to shorten the cardiopulmonary bypass time, and a tight perioperative glucose control [21] may help to reduce the incidence of postoperative renal dysfunction. Nacetylcysteine, B-type natriuretic peptide and other drugs have been proposed to reduce postoperative AKI or improve the renal function, however their use has been controversial [4].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, some preoperative and intraoperative preventive actions may help to prevent the postoperative renal dysfunction. Postponing the operation to improve the hemodynamic situation [19], stopping medications, such as angiotensin-converting enzyme inhibitors/angiotensin receptor blockers, shortly before the operation [20], planning the surgical strategy to shorten the cardiopulmonary bypass time, and a tight perioperative glucose control [21] may help to reduce the incidence of postoperative renal dysfunction. Nacetylcysteine, B-type natriuretic peptide and other drugs have been proposed to reduce postoperative AKI or improve the renal function, however their use has been controversial [4].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a reduction in the need for RRT in medical patients could be explained by the higher illness severity with more renal dysfunction on admission, precluding an impact of this mainly protective intervention [185]. Two large sequential cohort studies, one in a medical-surgical ICU [186] and the other in the setting of cardiac surgery [187], also revealed a significant reduction in observed renal dysfunction after the implementation of tight glycemic control. Finally, a recent meta-analysis indicated that survival benefit by applying tight glycemic control, if any, may be restricted only to patients in surgical ICUs [188].…”
Section: Vasodilatorsmentioning
confidence: 99%
“…2,[7][8][9][10][11][12][20][21][22]24,25 The authors of the remaining four articles did not find statistically significant association between peri-operative hyperglycemia and patient mortality. 13,18,19,23 Table 1 summarizes the main characteristics of the reviewed articles for this study.…”
Section: Resultsmentioning
confidence: 87%
“…As mentioned above, out of 16 reviewed articles in our study, 2,7-13,18-25 12 have as their main finding the association of hyperglycemia and inadequate BG control with increased mortality rates, either in-hospital or within 30 days. 2,[7][8][9][10][11][12][20][21][22]24,25 In the remaining four articles 13,18,19,23 the investigators did not find a statistically significant correlation between perioperative hyperglycemia or/and poor glycemic control and patient mortality, although Lazar et al 13 observed a significant survival advantage over the initial 2 years after surgery for patients with tight peri-operative glucose control. In addition, we could find a point of great interest in the findings of the study by Gandhi et al,18 in which the authors not only did not observe a significant correlation between tight glucose control for normoglycemia and 30-day mortality, but also concluded that there was a statistically significant increase in the incidence of death in the intensive insulin treatment patient group.…”
Section: Discussionmentioning
confidence: 97%